Pengaruh Teknik Permainan Menyusun Kata Terhadap Kemampuan Membaca Permulaan Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas I UPTD SD Negeri 18 Mendobarat - Siski Marsanda; Romadon; Silvio Juliana Nabela (Universitas Muhammadiyah Bangka Belitung, 2025)
This study is motivated by the low early reading skills of first-grade students at UPTD SD Negeri 18 Mendobarat, particularly in recognizing letters, forming syllables, and constructing words. The purpose of this study is to determine the effect of the Word Construction Game Technique on early reading skills in the Indonesian Language subject among first-grade students at UPTD SD Negeri 18 Mendobarat. The research method used is an experimental